Sestrin 2 and AMPK Connect Hyperglycemia to Nox4-Dependent Endothelial Nitric Oxide Synthase Uncoupling and Matrix Protein Expression - Eid, Assaad A. (American Society for Microbiology, 2013)
Mesangial matrix accumulation is an early feature of glomerular pathology in diabetes. Oxidative stress plays a critical role in hyperglycemia-induced glomerular injury. Here, we demonstrate that, in glomerular mesangial cells (MCs), endothelial nitric oxide synthase (eNOS) is uncoupled upon exposure to high glucose (HG), with enhanced generation of reactive oxygen species (ROS) and decreased production of nitric oxide. Peroxynitrite mediates the effects of HG on eNOS dysfunction. HG upregulates Nox4 protein, and inhibition of Nox4 abrogates the increase in ROS and peroxynitrite generation, as well as the eNOS uncoupling triggered by HG, demonstrating that Nox4 functions upstream from eNOS. Importantly, this pathway contributes to HG-induced MC fibronectin accumulation. Nox4-mediated eNOS dysfunction was confirmed in glomeruli of a rat model of type 1 diabetes. Sestrin 2-dependent AMP-activated protein kinase (AMPK) activation attenuates HG-induced MC fibronectin synthesis through blockade of Nox4-dependent ROS and peroxynitrite generation, with subsequent eNOS uncoupling. We also find that HG negatively regulates sestrin 2 and AMPK, thereby promoting Nox4-mediated eNOS dysfunction and increased fibronectin. These data identify a protective function for sestrin 2/AMPK and potential targets for intervention to prevent fibrotic injury in diabetes.